Identifikasi Faktor Penyebab Penumpukan Berkas Rekam Medis Aktif di RS Husada Utama - Nurul Kamilia; Rossalina Adi Wijayanti; Ida Nurmawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Based on the results of a preliminary study conducted at the Husada Utama Hospital it is known that in 2018 there was an accumulation of active medical record files which were 310 files. The impact of the accumulation of medical record files is the provision of medical record files will take longer so that patients often complain, officers become fatigued quickly in doing their work so that it will also have an impact on the depreciation process that should be done every day, and officers also feel uncomfortable and disturbed because the accumulation of medical record files also interferes with access to filing officers when retrieving and returning medical record files. This study aims to identify the factors causing the accumulation of active medical record files in Husada Utama Hospital. This type of research uses qualitative and data collection by interview, observation, and documentation. The results obtained that the results showed that the cause of the accumulation of medical record files that affect from the Man side is that the officer has never attended medical records training, from the Money side that is still not getting a budget for storage shelves, from the Material side there is a medical record file that is not using a map, in terms of Machine that is the number of storage racks not according to needs and in terms of Method which is the implementation of a storage system, alignment, and retention that is not in accordance with the Standard Operating Procedure (SOP).